2019
DOI: 10.1111/febs.14752
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of the CUBAN domain in the recognition of ubiquitin and NEDD8

Abstract: Among the members of the ubiquitin‐like (Ubl) protein family, neural precursor cell expressed developmentally down‐regulated protein 8 (NEDD8) is the closest in sequence to ubiquitin (57% identity). The two modification mechanisms and their functions, however, are highly distinct and the two Ubls are not interchangeable. A complex network of interactions between modifying enzymes and adaptors, most of which are specific while others are promiscuous, ensures selectivity. Many domains that bind the ubiquitin hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
87
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(99 citation statements)
references
References 59 publications
12
87
0
Order By: Relevance
“…By panning a human brain phage-displayed cDNA library using ubiquitin as bait, we identified a shorter fragment of N4BP1 (aa 813-896) that shows ubiquitin binding features and we further reduced the functional region to the last 50 amino acids of human N4BP1 (847-896aa) by means of biochemical approaches. Based on mutational analysis, we have shown that the interaction between N4BP1 and ubiquitin involves the Ile44-hydrophobic patch [11], in analogy with what has been observed in the majority of the UBDs characterized so far.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…By panning a human brain phage-displayed cDNA library using ubiquitin as bait, we identified a shorter fragment of N4BP1 (aa 813-896) that shows ubiquitin binding features and we further reduced the functional region to the last 50 amino acids of human N4BP1 (847-896aa) by means of biochemical approaches. Based on mutational analysis, we have shown that the interaction between N4BP1 and ubiquitin involves the Ile44-hydrophobic patch [11], in analogy with what has been observed in the majority of the UBDs characterized so far.…”
Section: Introductionsupporting
confidence: 64%
“…Interestingly, the minimal ubiquitin-binding region in N4BP1, including residues 849-896, shares 40% identity with the evolutionary related CUBAN domain, recently identified in the evolutionary related KHNYN protein [11]. The CUBAN has been shown to bind NEDD8 with an affinity that is higher than the value measured for monomeric ubiquitin [11]. In addition to interacting with neddylated cullins thanks to the direct recognition of the NEDD8 molecule, the CUBAN domain binds ubiquitin chains and polyubiquitinated proteins.…”
Section: A Novel Ubiquitin-binding Domain At the C-terminal End Of Humentioning
confidence: 98%
See 3 more Smart Citations